Silk micrococoons for protein stabilisation and molecular encapsulation - Ulyana Shimanovich (Nature Portfolio, 2017)
Silk fibres currently used in biotechnology are chemically reconstituted silk fibroins (RSF), which are more stable than native silk fibroin (NSF) but possess different biophysical properties. Here, the authors use microfluidic droplets to encapsulate and store NSF, preserving their native structure.